IQGAP1 Is Important for Activation of Caspase-1 in Macrophages and Is Targeted by Yersinia pestis Type III Effector YopM - Lawton K. Chung (American Society for Microbiology, 2014)
ABSTRACT YopM is a leucine-rich repeat (LRR)-containing effector in several Yersinia species, including Yersinia pestis and Y. pseudotuberculosis. Different Yersinia strains encode distinct YopM isoforms with variable numbers of LRRs but conserved C-terminal tails. A 15-LRR isoform in Y. pseudotuberculosis YPIII was recently shown to bind and inhibit caspase-1 via a YLTD motif in LRR 10, and attenuation of YopM− YPIII was reversed in mice lacking caspase-1, indicating that caspase-1 inhibition is a major virulence function of YopMYPIII. To determine if other YopM proteins inhibit caspase-1, we utilized Y. pseudotuberculosis strains natively expressing a 21-LRR isoform lacking the YLTD motif (YopM32777) or ectopically expressing a Y. pestis 15-LRR version with a functional (YopMKIM) or inactivated (YopMKIM D271A) YLTD motif. Results of mouse and macrophage infections with these strains showed that YopM32777, YopMKIM, and YopMKIM D271A inhibit caspase-1 activation, indicating that the YLTD motif is dispensable for this activity. Analysis of YopMKIM deletion variants revealed that LRRs 6 to 15 and the C-terminal tail are required to inhibit caspase-1 activation. YopM32777, YopMKIM, and YopMKIM deletion variants were purified, and binding partners in macrophage lysates were identified. Caspase-1 bound to YopMKIM but not YopM32777. Additionally, YopMKIM bound IQGAP1 and the use of Iqgap1−/− macrophages revealed that this scaffolding protein is important for caspase-1 activation upon infection with YopM− Y. pseudotuberculosis. Thus, while multiple YopM isoforms inhibit caspase-1 activation, their variable LRR domains bind different host proteins to perform this function and the LRRs of YopMKIM target IQGAP1, a novel regulator of caspase-1, in macrophages. IMPORTANCE Activation of caspase-1, mediated by macromolecular complexes termed inflammasomes, is important for innate immune defense against pathogens. Pathogens can, in turn, subvert caspase-1-dependent responses through the action of effector proteins. For example, the Yersinia effector YopM inhibits caspase-1 activation by arresting inflammasome formation. This caspase-1 inhibitory activity has been studied in a specific YopM isoform, and in this case, the protein was shown to act as a pseudosubstrate to bind and inhibit caspase-1. Different Yersinia strains encode distinct YopM isoforms, many of which lack the pseudosubstrate motif. We studied additional isoforms and found that these YopM proteins inhibit caspase-1 activation independently of a pseudosubstrate motif. We also identified IQGAP1 as a novel binding partner of the Yersinia pestis YopMKIM isoform and demonstrated that IQGAP1 is important for caspase-1 activation in macrophages infected with Yersinia. Thus, this study reveals new insights into inflammasome regulation during Yersinia infection.